2021
DOI: 10.1101/2021.04.07.438846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Brain Primary Cilia Length by MCH Signaling: Evidence from Pharmacological, Genetic, Optogenetic and Chemogenic Manipulations

Abstract: The melanin concentrating hormone (MCH) system is involved in numerous functions including energy homeostasis, food intake, sleep, stress, mood, aggression, reward, maternal behavior, social behavior, and cognition. MCH acts on a G protein-coupled receptor MCHR1, which expresses ubiquitously in the brain and localizes to neuronal primary cilia. Cilia act as cells' antennas and play crucial roles in cell signaling to detect and transduce external stimuli to regulate cell differentiation and migration. Cilia are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…We have recently demonstrated a high degree of circadian rhythmicity of cilia genes' expression across primate brain areas [23]. We also demonstrated that cilia length is highly dynamic in response to many internal and external stimulations, including genetic, optogenetic, chemogenetic, and chemical manipulations [24]. However, the age-dependent dynamics of cilia substructural and functional components are not known.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated a high degree of circadian rhythmicity of cilia genes' expression across primate brain areas [23]. We also demonstrated that cilia length is highly dynamic in response to many internal and external stimulations, including genetic, optogenetic, chemogenetic, and chemical manipulations [24]. However, the age-dependent dynamics of cilia substructural and functional components are not known.…”
Section: Introductionmentioning
confidence: 99%